Knowledge Management and Work Motivation as Determinants of Employee Performance: Evidence from a State-Owned Enterprise in Indonesia - Mutmainna Rachman; Kahar; Irwan Abdullah (Liquidity Jurnal Ilmu Manajemen dan Bisnis, 2026)
Employee performance is a strategic determinant of organizational effectiveness in State-Owned Enterprises, where accountability, efficiency, and public service outcomes are closely interconnected. This study aims to examine the effects of knowledge management and work motivation on employee performance within a public-sector organizational context. A quantitative explanatory design was employed using a census of 32 employees at a State-Owned Enterprise branch office. Data were collected through structured questionnaires and analyzed using multiple linear regression to test the partial and simultaneous influence of knowledge management and work motivation on employee performance. The findings indicate that work motivation has a positive and statistically significant effect on employee performance, confirming the importance of motivational mechanisms in enhancing productivity and engagement within bureaucratic institutions. In contrast, knowledge management demonstrates a statistically significant negative relationship with performance. This unexpected result suggests that ineffective implementation, cultural resistance, inadequate technological integration, or knowledge overload may undermine the potential benefits of knowledge management practices. Simultaneously, both variables significantly explain variations in performance outcomes, highlighting their strategic relevance. In conclusion, the study emphasizes that work motivation consistently strengthens employee performance, while knowledge management requires contextual alignment and effective execution to generate positive outcomes. These findings contribute to the refinement of human resource management strategies in public-sector organizations and underscore the importance of integrating motivational systems with well-designed knowledge management practices..